Інноваційне освітнє середовище як умова розвитку професійної компетентності педагогів - Ткачук, Надія; Tkachuk, Nadiya. (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті розкрито важливість урахування умов інноваційного освітнього середовища навчального закладу щодо розвитку професійної компетентності педагогів. Проаналізовано поняття інноваційне освітнє середовище; запропоновано досвід формування готовності педагогів до інноваційної діяльності як складової частини інноваційного освітнього середовища.Анализируються научно-теоретические подходы к сущности инновационной образовательной среды. Учитывая обобщения научных позиций по структуре инновационной образовательной среды, сделан акцент на личности педагога как важнейшей его составляющей. Путём анализа критериев инновационной среды обоснованы условия развития профессиональной компетентности педагогов. В контексте проекции теоретических положений предложен опыт научно-исследовательской лаборатории образовательных инноваций и координации деятельности РМК (ММК) Волынского ИППО по проблеме «Проектирование развития современного учебного заведения в условиях социокультурной среды региона». Определены основные ориентиры формирования готовности к инновационной деятельности: осознание педагогами необходимости введения педагогических инноваций в собственной практике, информированность о инновационных педагогических технологиях, знания новаторских методик, ориентированность на создание педагогами собственных новационных продуктов, готовность к преодолению трудностей, связанных с содержанием и организацией инновационной деятельности, создание информационных ресурсов. Предложен опыт школьной методической службы по содержанию, формам ее деятельности по развитию профессиональной компетентности педагога-новатора. Представлены отдельные позиции мониторинга результатов опытно-экспериментальной работы, подтверждающие, что такая деятельность способствует динамике профессиональных достижений педагогов, повышению рейтинга образовательного учреждения в социуме, результативности в сфере самореализации как педагогов, так и учеников. Сделан вывод о дальнейших исследованиях, которые будут затрагивать проведение оценки эффективности функционирования инновационной образовательной среды, изучение системных элементов и влияния внешних и внутренних факторов на его формирование.The analysis of scientific and theoretical approaches to the essence of innovative educational environment is covered. The article is focuses on the teacher’s personality as his essential component, considering generalization of scientific positions concerning the structure of the innovative educational environment. Conditions of development of teachers’ professional competence are proved through the analysis of innovative environment criteria. The experience of research laboratory of educational innovations and coordination of RMR (TMR) activities of Volyn In-Service Teacher Training Institute on “Designing of modern educational institution development in conditions of the sociocultural environment of the region” is offered. The main positions of formation of readiness for innovative activity are defined: awareness of needs of pedagogical innovations implementing to teachers’ practice, knowledge of innovative pedagogical technologies and techniques, focus on creation of teachers’ innovative products, readiness for overcoming of the difficulties connected with the contents and the organization of innovative activity, creation of information resources. School methodical service experience concerning the content and forms of its activities on the development of professional competence of the teacher and innovator is proposed. Separate positions of monitoring of research and experimental work results are acquainted, confirming that such activity promotes the dynamics of teachers’ professional achievements, a rating of educational institution in society, productivity in self-realization of teachers and pupils. The conclusion is drawn on further researches which will concern carrying out an assessment of efficiency functioning of the innovative educational environment, studying of system elements and influence of external and internal factors on its formation.
Innovative Educational Environment as Condition of Teachers’ Professional Competence Development.
Keywords: інноваційне освітнє середовище, готовність педагогів до інноваційної діяльності, дослідно-експериментальна діяльність, професійна компетентність; инновационная образовательная среда, готовность педагогов к инновационной деятельности, опытно-экспериментальная деятельность, профессиональная компетентность.; innovative educational environment, readiness of teachers for innovative activity, research and experimental activity, professional competence